A photovoltaic window with sun-tracking shading elements towards maximum power generation and non-glare daylighting. (15th October 2018) - Gao, Yuan; Dong, Jianfei; Isabella, Olindo; Santbergen, Rudi; Tan, Hairen; Zeman, Miro; Zhang, Guoqi
Graphical abstract: Highlights: Rh/v is defined to estimate the potential of solar energy on the vertical area. Sun-tracking PV shading elements integrated with windows are modeled and analyzed. Novel optimum sun-tracking methods and cell layout are first proposed. Annual energy generation and average efficiency are improved by 27.40% and 19.17%. Optimum sun-tracking methods reveal great ability to protect glare from the sun. Abstract: Vertical space bears great potential of solar energy especially for congested urban areas, where photovoltaic (PV) windows in high-rise buildings can contribute to both power generation and daylight harvest. Previous studies on sun-tracking PV windows strayed into the trade-off between tracking performance and mutual shading, failing to achieve the maximum energy generation. Here we first build integrated models which couple the performance of sun-tracking PV windows to the rotation angles. Secondly, one-degree-of-freedom (DOF) and two-DOF sun tracking are mathematically proven to be not able to gain either maximum power generation or non-glare daylighting under reasonable assumptions. Then we derive the optimum rotation angles of the variable-pivot-three-degree-of-freedom (VP-3-DOF) sun-tracking elements and demonstrate that the optimum VP-3-DOF sun tracking can achieve the aforementioned goals. When the restriction of the proposed model is relaxed, the same performance can be achieved by the optimum one-DOF sun tracking with extended PV slats and particular design of cell layout, requiring less complicated mechanical structures. Simulation results of nine global cities show that the annual energy generation and average module efficiency are improved respectively by 27.40% and 19.17% via the optimum VP-3-DOF sun tracking over the conventional perpendicular sun tracking. The proposed optimum sun-tracking methods also reveal better protection against sun glare. The optimum VP-3-DOF sun tracking is also demonstrated to be applicable to horizontal PV windows, as those applied in the sun roof of a glass greenhouse.